Structural analysis of vee-cap sheet metal component - Afzal, Asif; Baig, Maugal Ahmed Ali; Khan, Sher Afghan; Abdul Rahim, Shebeer (International Organization of Scientific Research ( IOSR ), 2016)
In this work, analysis of draw component i.e Vee-Cap used in AC motor and other machines is carried out. 3D modeling of the draw component is carried out in Solid Works software. ANSYS 16 is employed for the structural analysis of the sheet metal component considered for present study. Angles 00and 30 at the corner of the draw angle are considered for analysis of the component in order to check the stress distribution at the bottom fillet, which is the most critical part of the component. The displacement of the component is also analyzed to check the plastic strain behavior of the component. From the structural analysis it is clear that the von-mises stress distribution is maximum at 00 and reduced for 30. Whereas, for displacement and plastic strain of the component reduces by increasing the clearance angle from 0 degrees to 3 degrees.